2018
DOI: 10.7150/thno.24003
|View full text |Cite
|
Sign up to set email alerts
|

OVOL2 links stemness and metastasis via fine-tuning epithelial-mesenchymal transition in nasopharyngeal carcinoma

Abstract: Rationale: Metastasis is the leading cause of disease-related death among patients with nasopharyngeal carcinoma (NPC). Mounting evidence suggest that epithelial-mesenchymal transition (EMT) is crucial for cancer cells to acquire metastatic ability. In this study, we aim to clarify the extent to which EMT is involved in various cancer properties and identify novel markers for predicting the prognosis of NPC patients.Methods: Two cellular models derived from the same NPC cell line with distinct metastasis abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 45 publications
(70 reference statements)
4
32
0
Order By: Relevance
“…The results of the KEGG pathway enrichment analysis and GO function annotation revealed that upregulated DEGs were mainly enriched in 'cell adhesion', 'cell division', 'mitosis,' 'mitotic cell cycle', 'ECM-receptor interaction' and 'human papillomavirus infection', whereas downregulated DEGs were mainly involved in 'axonemal dynein complex assembly', 'microtubule-based movement', 'metabolic pathways', 'Huntington's disease', 'fluid shear stress' and 'atherosclerosis' and 'chemical carcinogenesis'. Previous studies have demonstrated that upregulation or downregulation of specific genes may affect NPC cell invasion, metastasis, proliferation and apoptosis (28)(29)(30). This result is consistent with the fact that carcinoma cell invasion and metastasis are closely associated with abnormal cell adhesion and cell division (28)(29)(30).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The results of the KEGG pathway enrichment analysis and GO function annotation revealed that upregulated DEGs were mainly enriched in 'cell adhesion', 'cell division', 'mitosis,' 'mitotic cell cycle', 'ECM-receptor interaction' and 'human papillomavirus infection', whereas downregulated DEGs were mainly involved in 'axonemal dynein complex assembly', 'microtubule-based movement', 'metabolic pathways', 'Huntington's disease', 'fluid shear stress' and 'atherosclerosis' and 'chemical carcinogenesis'. Previous studies have demonstrated that upregulation or downregulation of specific genes may affect NPC cell invasion, metastasis, proliferation and apoptosis (28)(29)(30). This result is consistent with the fact that carcinoma cell invasion and metastasis are closely associated with abnormal cell adhesion and cell division (28)(29)(30).…”
Section: Resultssupporting
confidence: 86%
“…This result is consistent with the fact that carcinoma cell invasion and metastasis are closely associated with abnormal cell adhesion and cell division (28)(29)(30). Furthermore, cancer cell proliferation and apoptosis are closely associated with abnormalities in the mitotic cell cycle (28)(29)(30). A previous study indicated that colorectal cancer cells interact with stromal cells by producing ECM components, mediating direct cell-cell contact and secreting growth factors (31).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…For example, studies with a Snail-inducible expression system in prostate cancer cells has identified metabolic plasticity and asymmetrical dynamics during their EMT-MET cycle (Stylianou et al, 2019). Other studies, where re-expression of significant epithelial markers such as E-cadherin, OVOL2 and GRHL2 after their knockout may not obtain the same spectrum of reversion also suggests asymmetrical dynamics (Qi et al, 2018;Chung et al, 2019;. The concept of bet hedging had been observed in bacterial persistence under different environmental stimulations by generating mutationindependent phenotypic heterogeneity (Veening et al, 2008).…”
Section: Understanding Dynamics Of Emtmentioning
confidence: 99%
“…In this issue of Theranostics , Feng and colleagues describe the role of OVOL2, a member of the Ovo family of conserved zinc-finger transcription factors, in metastasis and the enrichment of stemness in NPC 7 . Although OVOL2 was cloned nearly 20 years ago 8 , compared to other transcription factors involved in EMT, much less is known about OVOL2.…”
mentioning
confidence: 99%